INSPIRASI KITAB SUCI UNTUK MENINGKATKAN HARGA DIRI (SELF ESTEEM) - Mursyid, Ali; Ananda Sahara Dara Dinanti (Journal of Innovation Research and Knowledge, 2025)
Low self-esteem in adolescents increases the risk of mental health disorders. Adolescence is a crucial period where self-concept can strengthen or weaken. This study aims to analyze the interpretation of Wahbah Az-Zuḥailī and Quraish Shihab on how to overcome low self-esteem, with the hope that it can be applied by today's society. This study uses a qualitative method based on library studies. Data collection techniques are carried out by collecting related scientific literature. The data is then analyzed using the content analysis method using a psychological approach based on Abu Zaid Al-Balkhi's cognitive theory. The findings of this study indicate that to overcome poor self-esteem, we must first have an optimistic outlook because optimism will give birth to optimism. Second, we must not give up because positive people view setbacks as opportunities to improve themselves. Third, guard your heart and mind because bad thoughts can arise from an uncomfortable heart. Fourth, strengthen your faith. Allah will elevate our status if we have strong faith. This strategy for overcoming poor self-esteem is consistent with the ideas of Quraish Shihab and Wahbah Az-Zuḥailī. in QS. Ali-'Imrān [3]: 146, QS. Yūsuf [12]: 87, QS. Az-Zumar [39]:53, QS. Ar-Ra'd [13]: 28, and Ali-'Imrān [3]: 139.